2012
DOI: 10.1371/journal.pone.0040495
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Circulating C3 Levels and Mesangial C3 Deposition Predict Renal Outcome in Patients with IgA Nephropathy

Abstract: Background and AimsMesangial C3 deposition is frequently observed in patients with IgA nephropathy (IgAN). However, the role of complement in the pathogenesis or progression of IgAN is uncertain. In this observational cohort study, we aimed to identify the clinical implications of circulating C3 levels and mesangial C3 deposition and to investigate their utility as predictors of renal outcomes in patients with IgAN.MethodsA total of 343 patients with biopsy-proven IgAN were enrolled between January 2000 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
113
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 40 publications
15
113
2
1
Order By: Relevance
“…Recently, Kim et al 39 showed that mesangial C3 deposition predicted renal outcome in patients with IgAN. However, owing to the slowly progressive nature of IgAN and our relatively small follow-up population, we failed to draw any convincing conclusions regarding the predictive value of rs6677604 and mesangial C3 deposition in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al 39 showed that mesangial C3 deposition predicted renal outcome in patients with IgAN. However, owing to the slowly progressive nature of IgAN and our relatively small follow-up population, we failed to draw any convincing conclusions regarding the predictive value of rs6677604 and mesangial C3 deposition in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to this in situ activation, a systemic complement activation has been suggested by several studies, including a negative correlation between circulating C3 and mesangial C3 deposition [12]. C3 levels in Caucasian patients with progressive IgAN are not noticeably reduced, while in Chinese and Japanese patients slightly reduced levels of complement (<90 mg/dl) have been detected in similar cases [12,13]. The ratio between IgA levels (frequently increased in patients with IgAN) and C3 levels (seldom changed and then only slightly decreased) has been reported to be of prognostic value in adults and children [14].…”
Section: Complement Activation In Iga Nephropathymentioning
confidence: 93%
“…Complement inhibiting factors acting in fluid phase according to the hypothesis of systemic activation have been investigated in patients with IgAN. In Asiatic patients an association was reported between C3 and FH levels, suggesting an active regulation of the alternative complement pathway even in cases of subclinical activation [12,13].…”
Section: What Triggers Complement Activation In Igan?mentioning
confidence: 94%
See 1 more Smart Citation
“…C3 levels in serum are usually normal but degradation products, such as iC3b-C3d, may be elevated, suggesting activation of the alternative pathway [13]. Furthermore, decreased circulatory C3 levels and increased C3 deposition were suggested to be predictors of worse outcome [14]. Complement activation may thus contribute to renal inflammation during progressive IgA nephropathy [15].…”
Section: Introductionmentioning
confidence: 99%